RAMAN IDENTIFICATION OF PIGMENTS IN THE WORK OF THE CHILEAN CONTEMPORARY VISUAL ARTIST IGNACIO GUMUCIO - Rodríguez-Gacitúa, Camila; Campos-Vallette, Marcelo; Celis, Freddy (Journal of the Chilean Chemical Society, 2016)
The main pigments in the painting by the Chilean artist Ignacio Gumucio were identified by using micro-Raman spectroscopy. Three works by the artist, two paintings with wooden stand and a wall painting were analyzed. Pigments were vibrationally identified from cross-section samples of the contemporary paints on wood Río and Saludo and the wall painting Mental. The blue color Raman bands corresponds to cooper phthalocyanine. In the green areas, the Raman signals were ascribed to the azopigment acetoacetic arylide and copper phthalocyanine; the green color is then the result of a combination of the yellow and blue pigments. Raman bands in the pink areas were assigned to the azopigment β-naphthol. The dark green color in the Saludo paint is due to a chlorinated copper phthalocyanine pigment. Other materials in the artworks were also identified: rutile (TiO2) in Saludo in white areas and calcite (CaCO3) in Mental and Río. On this basis and taking into account the identification of the state of conservation a protocol for the preservation of the artworks Río and Saludo can be assessed.